Effect of Temperature and Extraction Time on the Total Phenolic Content of 70% Ethanol Extract of Temu Giring Rhizome (Curcuma heyneana Valeton & Zijp.) - Dwi Susiloningrum; Yanulia Handayani; Luthfiana Nurulin Nafi’ah (LPPM Akafarma Sunan Giri Ponorogo, 2025)
Temu giring (Curcuma heyneana Valeton & Zijp.) is a type of medical plant in the form of rhizomes. The plant is from the Zingiberaceae family. Intersection giring rhizome has various activities including antioxidant, antiviral, antiaging, and antimicrobial. Temu giring rhizome has various activities including antioxidant, antiviral, phenolic, saponin, and essential oil. The purpose of this study was to determine the effect of temperature and time of extraction with UAE (Ultrasonic Assited Extraction) on the total phenolic content of the 70% ethanol extract of the rhizome of teemu giring by spectrophotometry. The results showed that the highest total phenolic content was at a temperature of 40°C with a time 20 minutes namely 2,33%GAE, while the lowest total phenolic content was at a temperature of 30°C with a time of 10 minute namely 1,24%GAE.